Proposals for the edition of the federal standard of sports training for the sport «Wrestling» - Latyshev S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to present recommendations on the revision of the Federal Standard of Sports Training for the sport «Wrestling». Methods and structure of the study. The work analyzed the content of the federal standard of sports training for the sport «wrestling» (order of the Ministry of Sports of the Russian Federation dated November 30, 2022 No. 1091). Results and conclusions. The analysis showed that the Standard needs to be finalized in accordance with the requirements of the theory and practice of training athletes in the following areas: first - the unification of types of sports training in the structure of the educational and training process, their volume and dynamics at the stages of sports training, second - standards for monitoring the level of special physical preparedness.